Guitar Music of Celso Garrido-Lecca: Modern Projections of Peruan Traditions - Filatova, Tetiana (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2022)
The relevance of the article is to deepen the analytical aspect of knowledge about Peruan guitar music of the late 20th – early 21st centuries in the context of the renewal of genre traditions of Andean music on the example of works by Celso Garrido-Lecca. Main objective of the study is to determine the influence of Peruvian traditions on the guitar music of Celso Garrido-Lecca in the conditions of modern creative contexts. The methodology includes methods of historical, comparative, phenomenological, structural and functional analysis for: contextual consideration of the composer's creative activity; study of genre and style elements of Peruvian music traditions of folk, professional and non-academic origin in their interaction with the academic language of new music; comparison of the genealogy of rhythmic structures and their manifestations in the researched works; correlation of associative-figurative series with timbral connotations, specific genres and intonation and chord patterns. Results and conclusions. The study of the guitar music of the contemporary Peruvian composer Celso Garrido-Lecca performed by masters of academic art opens interesting pages of the new South American repertoire. Loyalty to the folklore traditions of his country, the study of timbre specificity and aesthetics of the Andean sound, the organology of ancient aerophones and local analogues of the charango, the collective practice of music making, as well as the ethnic language elements of the music of the coastal regions have affected the author's guitar works. Household traditions of Peruvian culture are identified in the sound atmosphere of the new vocabulary of the European model - polytonal “collage” music layers, constructivist modal octatonic arrangements, in the context of serial elements and polystylistic overlays of “foreign” texts. The genealogy of the rhythms deciphered in the composer's guitar opuses indicates a closeness to specific genre features: the Andean rhythm formulas of the huáyno, the Afro-Peruvian festejo, the ancient figures of the landó, the Creole samacueca, the tondero and the marinera with Iberian roots. The author resorted to quoting folklore sources in "Popular Andean Dances" with their updating with musical means of modern vocabulary; imitated the timbres of Andean flute orchestras in the cycle “Poetics” in the guitar parts; introduced the Andean charango of the Ayacuchan model into the scores of the orchestral versions of his suites; in the part of the instrumental duet of charango and guitar. In Celso Garrido-Lecca's guitar works, syntheses of archaic thinking of folkloric Andean chants, hybrid origins of poetics of local Creole and Afro-Peruvian rhythms with new language and intonation paradigms of academic art are organically embodied. Research perspectives are seen in the study of the influence of Peruvian culture on the modern non-academic traditions.